Methods to evaluate resistance of cement-based materials against microbially induced corrosion: A state-of-the-art review. (October 2021) - Wu, Linping; Huang, Guangping; Liu, Wei Victor
Abstract: Microbially induced corrosion (MIC) is a serious issue for sewer structures worldwide. Many studies have been carried out to develop more durable cement-based materials under the MIC attack. Due to a lack of a standard, various methods have been tried in the evaluation of resistance of different cement-based materials against MIC. A review of existing evaluation methods is needed to summarize these methods and their pros and cons. Therefore, this paper aims to conduct a state-of-the-art review of the existing evaluation methods of resistance against MIC. First, a review was focused on experimental evaluation methods, including chemical immersion tests, microbiological simulation tests, and in-situ tests. Then, non-experimental evaluation methods were summarized, such as numerical modelling and data science. After that, the pros and cons were discussed and highlighted for various evaluation methods. It was concluded that none of the existing evaluation methods could adequately reproduce the MIC process with reasonably high practicality and a short evaluation duration. Future research is needed in the development of such an evaluation method. Highlights: A critical review was carried out on experimental evaluation methods. Indexes used in experimental evaluation methods were summarized and discussed. Other evaluation methods were reviewed: numerical modelling and data science. The pros and cons were discussed and highlighted for various evaluation methods.